The Meaning of Logical Programs - Mayoh, Brian H. (DAIMI Report Series, 1980)
The semantics of a programming language are given by a function M from Programs to Meanings. In this paper we bring some uniformity into the definition of logical programming languages like LUCID and PROLOG by specifying M in Logic -> (Control -> Meanings). We describe how a context-free grammar can be assigned to each logical program and we identify Control with the language generated by the grammar. After this reduction there is no difference between the semantics of logical and conventional programming languages.